2018
DOI: 10.2147/ppa.s146268
|View full text |Cite
|
Sign up to set email alerts
|

Does knowledge on diabetes management influence glycemic control? A nationwide study in patients with type 1 diabetes in Brazil

Abstract: ObjectiveThe purpose of this study is to establish demographic and clinical data associated with the knowledge on diabetes management and its influence on glycemic control in patients with type 1 diabetes.MethodsThis was a retrospective, observational, multicenter study conducted with 1,760 patients between August 2011 and August 2014 in 10 cities of Brazil.ResultsOverall, 1,190 (67.6%) patients knew what glycated hemoglobin (HbA1c) means. These patients were older, had longer disease duration, longer follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
1
22
1
2
Order By: Relevance
“…This is an important finding as research has previously shown that diabetes knowledge is related with successful self-management and health outcomes. 91,92 On the contrary, we found that health literacy had a positive impact on self-care activities only for studies that assessed literacy with perception-based measures. The same result was found in subgroup analyses for two specific self-care activities: exercise and food care, but not for diet and blood monitoring.…”
Section: Discussioncontrasting
confidence: 72%
“…This is an important finding as research has previously shown that diabetes knowledge is related with successful self-management and health outcomes. 91,92 On the contrary, we found that health literacy had a positive impact on self-care activities only for studies that assessed literacy with perception-based measures. The same result was found in subgroup analyses for two specific self-care activities: exercise and food care, but not for diet and blood monitoring.…”
Section: Discussioncontrasting
confidence: 72%
“…Identical findings were portrayed by two novel studies. First, Gomes M et al (2018) [37] revealed that self-management of T1DM among young people was associated with higher age, more years of school attendance, lower reported rates of hypoglycemia and better glycemic control. Second, Ryan M (2014) [38] found that age was significantly correlated with diabetes self-care practices score.…”
Section: Discussionmentioning
confidence: 99%
“…Concurred findings were shown by four recent studies. First, Gomes M et al (2018) [37] portrayed that DM related knowledge was associated with lower rates of severe hypoglycemia, more years of school attendance and economic status. Second, Moskovitz A et al (2018) [45] revealed that better knowledge score of the studied diabetic adolescents was significantly associated with longer duration of contracting the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent degenerative complications are acute myocardial infarction, peripheral arteriopathy, stroke, and microangiopathy (AMÉRICO and ROCHA, 2020;CORTEZ et al, 2015). However, it is well established that these complications of T1DM can be avoided when glycemic control is adequate (GOMES et al 2018).…”
Section: Introductionmentioning
confidence: 99%